Lithology and Coal Seam Interpretation Using Qualitative Analysis Based On Gamma-Ray and Density Log Data at “Puy” Pit In West Banko Mining Area - Zidane Anung Andita; Ivana Jayarani Sitompul; Rahmat Catur Wibowo (Jurnal Rekayasa Lampung, 2026)
Coal is one of the alternative energy sources for petroleum that can be used as a more economical substitute fuel. The potential of coal in Indonesia is huge and is one of the promising potentials to be developed, considering its abundant availability. Well logging is a geophysical method used to obtain precise subsurface lithology data. The concept of well logging is to identify rock characteristics through the response of log data in the wellbore at the exact depth point to obtain information on location and thickness. This study aims to interpret coal layers based on geophysical log data and rock core photos to determine the lithology in the research area and identify the presence of coal seams. In this practical work, four wells were used with gamma-ray log data, density logs, and core photos, and WellCad Software was used to pick subsurface lithology. The subsurface lithology obtained is Claystone, Siltstone, Sandstone, and Coal. The existence of each Coal Seam can then be identified based on its keybed, where between Seam A1 and A2 there is a layer of Tuffaceous Sandstone, then between Seam A2 and B1 is characterised by a keybed in the form of Suban Marker, then between Seam B1 and B2 is separated by a layer of Carbonaceous Sandstone. Finally, between Seam B1 and C layers, there is a layer of Glauconite Sandstone lithology.